Lives in Peace Research The Oslo Stories - Tønnesson, Stein (Evidence-Based Approaches to Peace and Conflict Studies, 2022)
This open access book explains how PRIO, the world's oldest peace research institute, was founded and how it survived through crises. In this book, twenty-four of its researchers and associates, including Johan Galtung, Ingrid Eide, and Mari Holmboe Ruge, who founded the institute back in 1959, tell the stories of their roles in inventing and developing peace research. They reflect on their personal experiences with peace and conflict, tell what drove their peace engagement, and discuss the balance sought in the field between the cold dictates from academic rigor and the hot pursuit of peace, a desire for research to make a positive difference. Most of the chapters are interviews where one colleague interviews another. Some are self-reflective essays, while others are memorial essays written about a peace researcher who has passed away. Taken together, the book presents a lively picture of a thriving world-leading research environment and a wealth of conflicting or mutually reinforcing perspectives on war, violence, conflict, conflict management and resolution, negotiations and mediation, peacemaking, peace building, and the contested concept of peace. "The Oslo Stories is an indispensable source to the history of peace research." Dr. Olav Njølstad, Director, Nobel Institute, Oslo